Compliance with surgical antibiotic prophylaxis guidelines: a prospective descriptive study at a tertiary level hospital in Cape Town, South Africa - Schuster, Delia (Department of Anaesthesia and Perioperative Medicine, 2021)
Background: The aim of surgical antibiotic prophylaxis (SAP) is to prevent surgical site infection (SSI) by administering an appropriate antimicrobial agent perioperatively. However, SAP may be associated with adverse effects and incurs added costs. The primary objective of this prospective study is to establish whether clinicians are adhering to existing perioperative antibiotic prophylaxis guidelines in terms of indication, dosage and timing of SAP. Secondary objectives are to determine the proportion of patients receiving inappropriate antibiotics; and to evaluate correct practice concerning re-dosing and duration of SAP. Methods: A cross-sectional prospective audit of the anaesthetic records and prescription charts of surgical patients was conducted at Groote Schuur Hospital, a tertiary level teaching hospital in Cape Town, South Africa, over a period of one week. Data were collected by anaesthetists – blinded to the study objectives – and the investigators; then captured on Excel spread sheets and compared to existing SAP guidelines. Descriptive statistics and binary logistic regression were used for analysis. Results: Of the 192 patients consented, 180 questionnaires were completed for data analysis. The median age of participants was 44.5 years (IQR: 31.5-58), with a preponderance of females (58.7%). SAP was administered in 149 cases (82.8%) and withheld in 31 (17.2%). This was appropriate in 91.9% (137/149) and 77.4% (24/31) respectively. Twelve patients (6.7%) received inappropriate antibiotics and in seven (3.9%) it was inappropriately withheld. Of the 156 patients who should have received SAP, choice of drug was correct in 121 (77.6%), dosage in 110 (70.5%) and timing in 87 (55.8%). Absolute compliance was achieved in 44.4% (80/180). Errors were mostly related to timing, re-dosing and duration of SAP. Conclusion: Anaesthetists and surgeons at Groote Schuur Hospital demonstrate variable adherence to surgical antibiotic prophylaxis guidelines. Interventions aimed at improving compliance are warranted.